Fabrication of lipid-modified drug nanocrystals loaded injectable hydrogel for breast cancer therapy - Kumar, Manish; Jha, Abhishek; Goswami, Pooja; Srivastava, Ritika; Manjit, Manjit; Bharti, Kanchan; Koch, Biplob; Mishra, Brahmeshwar (Discover nano, 2025)
The current study includes the design of soluplus stabilized, lipid-coated, and fucoidan-oleylamine conjugate modified paclitaxel nanocrystals. The nanocrystals (Lipid-NCs) were about 100 nm, homogeneous, stable and showed improved drug release compared to pure PTX. The nanocrystals were subsequently loaded in an in situ gel-forming hydrogel for the intratumoral injection. The resulting hydrogel exhibited a sol-form at the lower temperature of 2–8 °C while converted to a gel-form at the body temperature. The injectable hydrogel had a reasonable viscosity, an acceptable pH, good syringeability, and a quick sol–gel transition. The hydrogel demonstrated high payload potential, homogeneous distribution, and controlled long-term drug release. In vivo studies revealed the higher efficacy of Lipid-NCs hydrogel in tumor inhibition while avoiding systemic toxicity, compared to pure PTX-loaded hydrogel and intravenously administered PTX. In conclusion, nanocrystal-loaded hydrogel is a promising localized drug delivery system for breast cancer therapy. Graphical abstract